Changes in microbial communities and nutrient content of rice straw compost caused by sterilization and their impact on plant growth - Cahyani Vita Ratri; Nugraheni Desriana; Yahya Elza Shafa (BIO Web of Conferences)
Compost, which plays a crucial role in sustainable farming systems, is produced through composting, an aerobic process mediated by microorganisms that decompose organic matter and typically involves a thermophilic phase. Compost functions as both a source of nutrients and organic matter and as a reservoir of beneficial microorganisms. However, the impact of compost, whether containing microorganisms or not, remains unclear. This study evaluated the impact of sterilization on rice straw (RS) compost and its influence on the growth of rice, maize, and peanut. RS-compost was produced over 60 days by adding Azolla, EM-4 and molasses. The compost was divided into sterilized (multistage autoclaving, 3 times over 3 consecutive days) and non-sterilized treatments. Sterilization reduced microbial populations in the compost significantly (0-5.1 × 105 CFU/g vs. 2.9-836.7 × 105 CFU/g) but increased nutrient content, notably total nitrogen (128.57%) and available potassium (84.4%), while reducing organic carbon (4.9%). Greenhouse experiment showed the application of non-sterilized compost significantly boosted dry weights of rice (142.01%), maize (29.22%), and peanut (8.78%) compared to sterilized compost. These findings highlight the critical role of indigenous microorganisms in enhancing RS-compost functionality and plant growth. This approach is critical for fundamental research on compost treatments, which host diverse microorganisms with multifunctional roles that influence the final outcomes.